2014
DOI: 10.1016/j.agee.2013.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Responses of predatory invertebrates to seeding density and plant species richness in experimental tallgrass prairie restorations

Abstract: a b s t r a c tIn recent decades, agricultural producers and non-governmental organizations have restored thousands of hectares of former cropland in the central United States with native grasses and forbs. However, the ability of these grassland restorations to attract predatory invertebrates has not been well documented, even though predators provide an important ecosystem service to agricultural producers by naturally regulating herbivores. This study assessed the effects of plant richness and seeding densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
(55 reference statements)
1
12
0
2
Order By: Relevance
“…Although ants are highly associated with dominant vegetation types (e.g. forests vs. grasslands), most studies have found little to no relationship with plant richness or cover within a given vegetation type (Hill et al, 2008;Nemec et al, 2014;Peters et al, 2016). Some studies have identified plant structure or vegetation height as a more important characteristic for predicting ants in grasslands (New, 2000;Debinski et al, 2011).…”
Section: Vegetationmentioning
confidence: 99%
“…Although ants are highly associated with dominant vegetation types (e.g. forests vs. grasslands), most studies have found little to no relationship with plant richness or cover within a given vegetation type (Hill et al, 2008;Nemec et al, 2014;Peters et al, 2016). Some studies have identified plant structure or vegetation height as a more important characteristic for predicting ants in grasslands (New, 2000;Debinski et al, 2011).…”
Section: Vegetationmentioning
confidence: 99%
“…Yet, despite their importance and potential utility in monitoring and a heightened interest in restoration within the past few decades, little research has focused on the impact of grassland restoration on spider communities in North America (Sampson & Knopf ; Nemec et al ). While more work has been conducted in European systems (see Bell et al , for review), European grasslands and their management and restoration differ in significant ways from U.S. systems, especially those in the arid and semiarid West.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to describe not only the spider communities present in an arid grassland in the western United States, but also to examine habitat variables that influence spiders in these communities. Unlike other studies that have focused on invertebrate responses to grassland/shrub‐steppe restoration (e.g., Mortimer et al ; Longcore ; Déri et al ; Borchard et al ; Nemec et al ), we focused on spiders specifically to enhance our ability to pinpoint habitat variables underlying responses of different species of spiders to restoration. We assessed three treatments including native (or reference sites), degraded, and restored grassland habitat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study in 2013 found that increased inflorescence and vegetative growth, often encouraged by rainfall or increased available water, encouraged predatory arthropods to stay in patches for longer periods of time (Nemec et al 2014).…”
Section: Discussionmentioning
confidence: 95%